La prison est-elle obsolète ? - Davis, Angela; Peronny, Nathalie (Au diable vauvert, 2014)
"Comment et pourquoi plus de deux millions d’américains sont aujourd’hui derrière les barreaux ? Comment les entreprises font-elles profit du système carcéral ? Quels sont les mécanismes qui conduisent à criminaliser les communautés de couleur et à désaffilier politiquement de larges franges d’électeurs dans les minorités ? Comment et pourquoi plus de deux millions d'américains vivent en prison ? Comment les entreprises font-elles profit du système carcéral ? Quels sont les mécanismes qui criminalisent les communautés de couleur et désaffilient politiquement les électeurs des minorités ?
Keywords: afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; capitalisme; cours; discipline; droits civiques; esclavagisme; féminismes noirs; histoire et politique; inégalités; justice sociale; militance; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Bananas, beaches and bases: making feminist sense of international politics - Enloe, Cynthia H. (University of California Press, 2014)
In this brand new radical analysis of globalization, Cynthia Enloe examines recent events—Bangladeshi garment factory deaths, domestic workers in the Persian Gulf, Chinese global tourists, and the UN gender politics of guns—to reveal the crucial role of women in international politics today. With all new and updated chapters, Enloe describes how many women's seemingly personal strategies—in their marriages, in their housework, in their coping with ideals of beauty—are, in reality, the stuff of global politics. Enloe offers a feminist gender analysis of the global politics of both masculinities and femininities, dismantles an apparently overwhelming world system, and reveals that system to be much more fragile and open to change than we think.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; inégalités; pol5480; politique internationale; premier cycle; ressource en ligne; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; travail

Sapphic fathers: Discourses of same-sex desire from nineteenth-century France - Schultz, Gretchen (University of Toronto romance series, 2014)
Literature that explored female homosexuality flourished in late nineteenth-century France. Poets, novelists, and pornographers, whether Symbolists, Realists, or Decadents, were all part of this literary moment. In Sapphic Fathers, Gretchen Schultz explores how these male writers and their readers took lesbianism as a cipher for apprehensions about sex and gender during a time of social and political upheaval. Tracing this phenomenon through poetry (Baudelaire, Verlaine), erotica and the popular novel (Belot), and literary fiction (Zola, Maupassant, Péladan, Mendès), and into scientific treatises, Schultz demonstrates that the literary discourse on lesbianism became the basis for the scientific and medical understanding of female same-sex desire in France. She also shows that the cumulative impact of this discourse left tangible traces that lasted well beyond nineteenth-century France, persisting into twentieth-century America to become the basis of lesbian pulp fiction after the Second World War.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires